Perancangan User Interface Sistem Informasi Akademik Sekolah berbasis Website pada SD AL-Manar Surabaya menggunakan Metode Goal Directed Design (GDD) - Fairuz Salsabila Rofiq; Hanifah Muslimah Az-Zahra; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
SD Al-Manar Surabaya needs a good user interface design and easy to use by everyone especially the school. The designed interface will be used as guidelines for implementing the academic information system website at SD Al-Manar Surabaya. This study aims to produce a user interface design for an academic information system website at SD Al-Manar Surabaya using the Goal Directed Design (GDD) method. From this research, a prototype user interface for an academic information system website was produced at SD Al-Manar Surabaya. After that, a final evaluation was carried out on the prototype which was made using usability testing on 5 respondents from each user and filling out the System Usability Scale (SUS) questionnaire for 20 respondents. Usability testing is based on three aspects, namely effectiveness, efficiency, and satisfaction. Usability testing gets suggestions or feedback from respondents regarding the prototype made. The final results of this study produced a website user interface prototype for SD Al-Manar Surabaya academic information system which has an effectiveness value of 93.32% for admin, 90% for teachers, and 88.56% for student guardians. Time-based efficiency values ​​were 0.0893 goals/second for admins, 0.08348 goals/second for teachers, and 0.09343 goals/second for student parents. To measure user satisfaction using the SUS questionnaire with an overall result of 82.125 which is worth B in the excellent category.